2017
DOI: 10.1097/md.0000000000009225
|View full text |Cite
|
Sign up to set email alerts
|

A successful insertion of PICC in patient with cardiac angiosarcoma and neoplasty of right atrium and pacemaker

Abstract: Introduction:Primary cardiac angiosarcoma is a rare tumor and the common treatment is surgical resection followed by chemotherapy. Peripherally inserted central venous catheters (PICCs) are widely used in cancer patients and ultrasound-guided PICC insertion could improve success rate especially in patient with abnormal anatomy structure. Reports about PICCs being placed in patient who had suffered from the cardiac angiosarcoma and neoplasty of right atrium with an ipsilateral cardiac permanent pacemaker are ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…16 "Presence of another CVC when index PICC placed" was rare in our study, although we had reported that PICC could be inserted in patient with ipsilateral cardiac permanent pacemaker for chemotherapy. 17 In clinical practice, we found that CVC may interfere with PICC guide wires and it was reported that several vascular devices in the same intraluminal space may lead to catheter entanglement and difficult to removal. 18 WBC at the time of PICC placement had been included in study of the MRS, while D-dimer was not involved.…”
Section: Discussionmentioning
confidence: 95%
“…16 "Presence of another CVC when index PICC placed" was rare in our study, although we had reported that PICC could be inserted in patient with ipsilateral cardiac permanent pacemaker for chemotherapy. 17 In clinical practice, we found that CVC may interfere with PICC guide wires and it was reported that several vascular devices in the same intraluminal space may lead to catheter entanglement and difficult to removal. 18 WBC at the time of PICC placement had been included in study of the MRS, while D-dimer was not involved.…”
Section: Discussionmentioning
confidence: 95%
“…Despite its low incidence, the association of two malignancies in a single patient has been widely reported in the literature, while only a relatively small number (0.5%) of three malignancies have been described including primary cardiac sarcomas [ 30 - 32 ]. Some cases of cardiac sarcomas (pleomorphic spindle cell sarcoma, angiosarcoma) in pacemaker patients are described [ 16 , 33 ]. At the same time, there are no clinical reports of patients (with or without a cardiac pacemaker) with primary osteosarcoma of the heart after double carcinomas of the liver and prostate.…”
Section: Discussionmentioning
confidence: 99%
“…Peripherally inserted central catheter (PICC), located at the lower 1/3rd of the superior vena cava (SVC) and cavo-atrial junction, is commonly used in cancer patients. [1,2] Malpositioned catheters are associated with increased complications. [3] Persistent left superior vena cava (PLSVC), a vascular anomaly, has an incidence rate of 2%.…”
Section: Introductionmentioning
confidence: 99%